Group A Streptococcal Carriage and Seroepidemiology in Children up to 10 Years of Age in Australia. Issue 8 (August 2015) - Marshall, Helen S.; Richmond, Peter; Nissen, Michael; Lambert, Stephen; Booy, Robert; Reynolds, Graham; Sebastian, Shite; Pride, Michael; Jansen, Kathrin U.; Anderson, Annaliesa S.; Scully, Ingrid L.
Abstract : Background: Group A streptococci (GAS) and other β-hemolytic streptococci (BHS) cause pharyngitis, severe invasive disease and serious nonsuppurative sequelae including rheumatic heart disease and post streptococcal glomerulonephritis. The aim of this study was to assess carriage rates and anti-streptococcal C5a peptidase (anti-SCP) IgG levels and identify epidemiologic factors related to carriage or seropositivity in Australian children. Methods: A throat swab and blood sample were collected for microbiological and serological analysis (anti-SCP IgG) in 542 healthy children aged 0–10 years. Sequence analysis of the SCP gene was performed. Serological analysis used a competitive Luminex Immunoassay designed to preferentially detect functional antibody. Results: GAS-positive culture prevalence in throat swabs was 5.0% (range 0–10%), with the highest rate in 5 and 9 years old children. The rate of non-GAS BHS carriage was low (<1%). The scp gene was present in all 22 isolates evaluated. As age of child increased, the rate of carriage increased; odds ratio, 1.14 (1.00, 1.29); P = 0.50. Geometric mean anti-SCP titers increased with each age-band from 2 to 7 years, then plateaued. Age, geographic location and number of children within the household were significantly associated with the presence of anti-SCP antibodies. Conclusions: Children are exposed to GAS and other BHS at a young age, which is important for determining the target age for vaccination to protect before the period of risk.